Defining and Dividing the Greater Caribbean: Insights from the Biogeography of Shorefishes - Robertson, D. Ross; Cramer, Katie L. (PloS one, 2014)
The Greater Caribbean biogeographic region is the high-diversity heart of the Tropical West Atlantic, one of four global centers of tropical marine biodiversity. The traditional view of the Greater Caribbean is that it is limited to the Caribbean, West Indies, southwest Gulf of Mexico and tip of Florida, and that, due to its faunal homogeneity, lacks major provincial subdivisions. In this scenario the northern 2/3 of the Gulf of Mexico and southeastern USA represent a separate temperate, "Carolinian" biogeographic region. We completed a comprehensive re-assessment of the biogeography of the Greater Caribbean by comparing the distributions of 1,559 shorefish species within 45 sections of shelf waters of the Greater Caribbean and adjacent areas. This analysis shows that that the Greater Caribbean occupies a much larger area than usually thought, extending south to at least Guyana, and north to encompass the entire Carolinian area. Rather than being homogenous, the Greater Caribbean is divided into three major provinces, each with a distinctive, primarily tropical fauna: (1) a central, tropical province comprising the West Indies, Bermuda and Central America; (2) a southern, upwelling-affected province spanning the entire continental shelf of northern South America; and (iii) a northern, subtropical province that includes all of the Gulf of Mexico, Florida and southeastern USA. This three-province pattern holds for both reef- and soft bottom fishes, indicating a general response by demersal fishes to major variation in provincial shelf environments. Such environmental differences include latitudinal variation in sea temperature, availability of major habitats (coral reefs, soft bottom shorelines, and mangroves), and nutrient additions from upwelling areas and large rivers. The three-province arrangement of the Greater Caribbean broadly resembles and has a similar environmental basis to the provincial arrangement of its sister biogeographic region, the Tropical Eastern Pacific.